The Trade Policy of Emerging Countries - Marianna Restum Antonio de Albuquerque (Brazilian Political Science Review, 2017)
As the World Trade Organization (WTO) and its predecessor, the General Agreement on Tariffs and Trade (GATT) has stimulated the access to new markets and enhanced the basis of non-discrimination and reciprocity in trade policies, it is easy to consider that this new economic and commercial order has been beneficial to emerging powers. These countries were able to expand their domestic productions and compete on more equal terms with developed countries. In her book, "The Trade Policy of Emerging Countries: Strategic Choices of Brazil and India", Laura Carsten Mahrenbach departs from these assumptions, and instead pursues the objective of analyzing how domestic variables, such as economic interests and political ideas, are reflected in strategic choices made by two emerging powers, Brazil and India, in WTO negotiations.